Facettes de l'exil dans la diaspora féminine roumaine contemporaine - Iulia ROMAN (ACROSS)
The transformation of self in connection with space highlights a heightened sensitivity to the external world in relation to human identity. This interdependence, in which the geographical boundaries impose themselves as essential conditions for existence, intersects with identity, which perpetually seeks to distinguish itself from others and establish a sense of belonging. These dual aspects offer a unique perspective on how space is perceived. The DNA of selfhood lies in sensitivity, in the capacity to connect with others and, crucially, with the land itself. This exploration delves into the theme of exile, identifying and analysing the characteristics of voluntary or involuntary departure onto foreign soil through a literary lens.